Association of the Arginase Ι with Bronchial Asthma (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
Objective The aim of this study was to detect the arginase Ι (ARG I) enzyme in asthma patients, clarify its role, in addition to examining the relationship of this enzyme with bronchial asthma.Methods:Blood samples were collected from 100 patients from the Department of Medicine in Rizgary Hospital in Erbil City, in addition to intact 100 volunteers; the introduced questionnaire was filled out on the basis of type-induced asthma, duration of the disease, age of the patients, gender, family history, and allergy condition, Serum was separated to perform Enzyme-linked immunosorbent assay (ELISA) in Medical Research Center to examine the association of ARGΙ with bronchial asthma. By ARG activity we can measure the conversion of arginine to ornithine and urea. By using a quantitative colorimetric assay at 490 nm, employing a QuantiChrom arginase assay kit (Bioassay Systems).Results: Our results depicted the association between ARGΙ and bronchial asthma: based on their age, significant elevation of serum arginase level was observed in the patients with ≥81 years old, which mean value (100.16±19.77c), p-value (0.000); also the duration of asthma ≥20 years (82.48±38.81c) , p-value (0.01) were remarkably affected; this sign was found in those with types of induced asthma and with allergy condition.  But the non- significant difference in the frequency of abnormal serum arginase level was observed in those patients that have a family history of asthma disease and gender of the patients. This finding demonstrated a remarkable association of ARG Ι in the development of asthma at p ˂ 0.05.